Design of network traffic monitoring and control system in SDN - Chuan LIU; Zheng LOU; Hui HUANG; Hui DENG (Dianxin kexue)
The core idea of SDN（software defined networking）is that the control plane and data plane are separated,which makes the network traffic can be flexible controlled.Since SDN has these characteristics,the traffic monitoring and control in SDN have significant differences with traditional IP networks.A network traffic monitoring and control system based on sFlow technology was presented.With the application of sFlow,the process of data collection was separated from the control plane of SDN.The experimental environment was constructed based on OpenDaylight controller and Mininet,and the abnormal traffic was simulated by DoS（denial of service）attacks.The experiments show that the proposed network traffic monitoring and control system can effectively intercept the abnormal traffic.